2011
DOI: 10.1007/s00216-011-5496-z
|View full text |Cite
|
Sign up to set email alerts
|

A high throughput glucocerebrosidase assay using the natural substrate glucosylceramide

Abstract: Glucocerebrosidase is a lysosomal enzyme that catalyzes the hydrolysis of glucosylceramide to form ceramide and glucose. A deficiency of lysosomal glucocerebrosidase due to genetic mutations results in Gaucher disease, in which glucosylceramide accumulates in the lysosomes of certain cell types. Although enzyme replacement therapy is currently available for the treatment of type 1 Gaucher disease, the neuronopathic forms of Gaucher disease are still not treatable. Small molecule drugs that can penetrate the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Another potential mechanism is that reduced GCase activity may increase a-syn phosphorylation at serine 129, a modification that has been shown to promote a-syn aggregation (Ferrer et al, 2011;Walker et al, 2013). Because of the function that GCase can catalyze the breakdown of GlcCer into glucose and ceramide (Motabar et al, 2012), a reduction in GCase activity will decrease the production of ceramide, an activator of PP2A (Chalfant et al, 1999;Dobrowsky et al, 1993), which functions as a dephosphorylation enzyme for a-syn. This will reduce PP2A activity, leading to an increase in a-syn phosphorylation and further aggregation (Fujiwara et al, 2002;Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism is that reduced GCase activity may increase a-syn phosphorylation at serine 129, a modification that has been shown to promote a-syn aggregation (Ferrer et al, 2011;Walker et al, 2013). Because of the function that GCase can catalyze the breakdown of GlcCer into glucose and ceramide (Motabar et al, 2012), a reduction in GCase activity will decrease the production of ceramide, an activator of PP2A (Chalfant et al, 1999;Dobrowsky et al, 1993), which functions as a dephosphorylation enzyme for a-syn. This will reduce PP2A activity, leading to an increase in a-syn phosphorylation and further aggregation (Fujiwara et al, 2002;Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Specific small molecules have shown to enhance the levels of the deficient lysosomal enzymes in several LSDs including GM2 gangliosidosis [12; 27] and Gaucher disease [12; 13; 14; 15; 16] by assisting the folding of mutant enzymes preventing their early degradation by ERAD. Other small molecules for Fabry disease and GM1 gangliosidosis had been characterized earlier [28].…”
Section: Discussionmentioning
confidence: 99%
“…In GLD, as in most LSDs, symptoms associated with the disease are only manifested if a mutation encodes a GALC mutant that works below a critical threshold, which is, in general, ~10% of wild type enzymatic activity [11]. Small molecules have been shown to assist the folding of misfolded mutant lysosomal enzymes resulting in enhancements of their residual enzymatic activity [12; 13; 14; 15; 16]. Thus, increases of the residual mutant GALC activity above the critical threshold should prevent the cytotoxic levels of psychosine, avoiding the oligodendrocyte apoptosis and the subsequent demyelination process.…”
Section: Introductory Statementmentioning
confidence: 99%
“…We have previously found that the activities of some glucocerebrosidase inhibitors, identified in enzyme assays using artificial substrate and recombinant enzyme, dramatically reduced in the natural substrate assay and cell-based assay [28]. An alternative compound screen using native enzyme extracted from patient tissue significantly improved the quality of glucocerebrosidase inhibitors discovered, and an improved correlation of compound activities between the enzyme assay and cell based assay was observed [28, 29]. …”
Section: Discussionmentioning
confidence: 99%